Foreword: An Early Paper on Atayal - Li, Paul Jen-kuei (The Archive; The Archive Classics: Legends of the Atayal People on Formosa, 2023)
Scheerer’s (1932) paper on Atayal in German is an early publication on Atayal. The earliest one is Ogawa’s (1931) Atayal Vocabulary in Japanese. Both are based on Squliq, the prestige dialect of Atayal. Each free lexical form usually contains no more than two vowels, as Squliq is spoken today. It is interesting to find that many of the recorded forms by Scheerer contain three or more vowels each, e.g., atayal ‘person’, kamaturu ‘leech’, tamariŋ ‘to work’, hamawak ‘to help along’. This seems to indicate that the Squliq dialect of Atayal still retained many vowels when Scheerer investigated it in 1930, less than a hundred years ago. He made some interesting observations. For instance, he noticed the free phonetic variant of s ~ h , as in musa ~ muha ‘to walk’. But he made a mistake of treating the two negatives, uka and uŋat , as free variants; the truth is that they are used in different dialects.